EFEKTIVITAS PERENCANAAN PEMBELAJARAN BERBASIS LITERASI DIGITAL UNTUK MENINGKATKAN MUTU LULUSAN DI SDN CIWANGI PURWAKARTA - Nina Herlina; Iis Nurmalasari; Dinny Mardiana; Suharyanto H Soro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low quality of graduates, which constitutes the main problem in the organization of education, particularly in terms of character, independent learning, and readiness to face global challenges. The low quality of graduates is influenced by weak planning of quality improvement programs that have not been formulated systematically and sustainably, where planning is not yet needs-based, data-driven, and oriented toward long-term goals, amid suboptimal implementation and achieved educational outcomes. The research aims to analyze the effectiveness of digital literacy learning planning in improving graduate quality through a Plan-Do-Check-Act (PDCA) management cycle approach, with emphasis on the planning (Plan) stage. The research employs a qualitative approach and descriptive analysis method, with data collection techniques consisting of in-depth interviews, observations, and document studies. The research findings indicate: 1) the planning stage encompasses needs analysis, quality goal setting, program development, and determination of success indicators; 2) digital literacy-based learning planning that applies the PDCA cycle is formulated participatively, measurably, and oriented toward student needs, integrated into the Learning Implementation Plan (RPP), and supported by adequate Information and Communication Technology (ICT) facilities, thereby serving as the primary foundation for improving graduate quality; 3) mature and structured planning proven to facilitate program implementation, strengthen the evaluation process, and drive sustainable graduate quality improvement. [Research conclusion,] digital literacy-based learning planning at SDN Ciwangi Purwakarta is effective in enhancing graduate quality..